Hunting in pre-Islamic Arabia in light of the epigraphic evidence - Maraqten, Mohammed (Arabian archaeology and epigraphy, 2015)
The hunting of wild animals for food, sport or for the defence of people and herds, was common in the ancient Near East, especially in early times. This paper gives a survey of hunting practices in pre-Islamic Arabia primarily from the beginning of the first millennium BCE to the eve of Islam in light of the epigraphic evidence and of rock art as well as archaeological discoveries.